2021
DOI: 10.1021/acsanm.1c02458
|View full text |Cite
|
Sign up to set email alerts
|

Single Nickel Atom-Modified Phosphorene Nanosheets for Electrocatalytic CO2 Reduction

Abstract: Nowadays, carbon dioxide (CO 2 ) produced by global energy consumption far exceeds what the environment can absorb. So, the world is seeking a way to control and reduce CO 2 emissions. The electrocatalytic CO 2 reduction reaction (CRR) can effectively convert this greenhouse gas into energy sources, thus providing a method to solve CO 2 emission and energy crisis issues. However, only quite limited catalysts are capable of converting CO 2 into high-value C1 products. Herein, four structures of single Ni atom-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 67 publications
(111 reference statements)
0
26
0
Order By: Relevance
“…Similarly, P atoms can also coordinate with other metallic centers making them suitable candidates for the supporting SA centers. 412 Luo et al synthesized gold SA decorated BP nanosheets (Au 1 /BP nanosheets) by injecting HAuCl 4 precursor in exfoliated BP suspension. 413 The color mapped HAADF-STEM image of 0.2 wt % Au 1 /BP nanosheets, displayed the atomic distribution of Au on the sheets (Figure 27a).…”
Section: Photoactive Sacs For Ch 4 Ormentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, P atoms can also coordinate with other metallic centers making them suitable candidates for the supporting SA centers. 412 Luo et al synthesized gold SA decorated BP nanosheets (Au 1 /BP nanosheets) by injecting HAuCl 4 precursor in exfoliated BP suspension. 413 The color mapped HAADF-STEM image of 0.2 wt % Au 1 /BP nanosheets, displayed the atomic distribution of Au on the sheets (Figure 27a).…”
Section: Photoactive Sacs For Ch 4 Ormentioning
confidence: 99%
“…These P atoms are easily oxidized under air/oxygen/water to form P–O and PO dangling bonds. Similarly, P atoms can also coordinate with other metallic centers making them suitable candidates for the supporting SA centers . Luo et al synthesized gold SA decorated BP nanosheets (Au 1 /BP nanosheets) by injecting HAuCl 4 precursor in exfoliated BP suspension .…”
Section: Photoactive Sacs For Ch4ormentioning
confidence: 99%
“…Compare to other metals anchored WTe 2 in this study and other CO 2 RR catalysts reported in the literature, Ni@WTe 2 possesses better catalytic performance to produce HCOOH (Table S1, Supporting Information). [46][47][48][49][50]…”
Section: Analysis Of C1 Product Generationmentioning
confidence: 99%
“…18 Preformed Ag, Au, Ni, Pd and Pt nanoparticles were loaded onto few-layer phosphorene and the observed superior performance in gas sensing, selective hydrogenation, oxidation and photocatalysis was attributed to the metal/phosphorene contact. [19][20][21][22][23][24] Phosphorene based single atom catalysts (SACs) were also proposed to be efficient in the partial oxidation of methane, 25 electrocatalytic nitrogen, CO and CO 2 reductions, [26][27][28][29][30][31] hydrogenation, 32 CO oxidation, 33,34 oxygen reduction/evolution and hydrogen evolution, 35 etc. However, the reported approaches for the fabrication of phosphorene based SACs are still limited to the atomic layer deposition with the reaction of high energy precursors with the phosphorene support that may result in defective or doped phosphorene, and the wet chemistry approach through liquid phase reduction of precursors, but further treatment is required.…”
Section: Introductionmentioning
confidence: 99%